NERC’s control performance standards based load frequency controller for a multi area deregulated power system with ANFIS approach - Abhijith Pappachen; A. Peer Fathima (Ain Shams Engineering Journal, 2018)
This paper presents the design of a North American Reliability Council (NERC) standards BAL-001-2 based Adaptive Neuro-Fuzzy Interface System (ANFIS) controller for multi-area deregulated power system under different contract scenarios. The proposed controller is tested on the Indian regional grid system and its control performance standards are compared with the conventional PID controller and ANFIS controller. The major objectives are (i) To find a suitable control for mitigating the diverse LFC problems in a deregulated power system (ii) to comply with the NERC control performance standards which are CPS1, CPS2 and BAAL, and (iii) to reduce the wear and tear of the generating units. Dynamic modelling of controllers, test system and simulation studies are performed using MATLAB/Simulink environment. The simulation results validate that the NERC standards based ANFIS controller is one of the best controller for the four area Indian regional grid under deregulated environment. Keywords: Load frequency control, Deregulation, NERC’s control performance standards, Balancing authority ACE limits, Adaptive neuro-fuzzy interface system